2005
DOI: 10.1007/pl00021542
|View full text |Cite
|
Sign up to set email alerts
|

Binocular, Monocular and Dichoptic Pattern Masking

Abstract: It has been reported that a quadratic summation rule can account for threshold versus masker contrast (TvC) functions for binocular, monocular and dichoptic masking. However, the present study suggests that inputs from two eyes are summed in different ways. Foley's model was revised to describe TvC functions for binocular, monocular and dichoptic masking. The revised model has the following two characteristics. First, the revised model receives two monocular inputs. Secondly, excitations and inhibitory signals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Our measurements using the method of constant stimuli indicated that the perceived contrast was 1.1 times higher at 1 degree uncrossed disparity. This elevation value is near increment thresholds for contrast discrimination within a range of high contrasts ( Legge & Foley, 1980 ; Maehara & Goryo, 2005 ; Meese et al, 2006 ). Thus, the observers would possibly notice subtle changes in the appearance of the luminance contrasts of stereoscopic patterns even if the actual contrasts were kept constant.…”
Section: Discussionmentioning
confidence: 68%
“…Our measurements using the method of constant stimuli indicated that the perceived contrast was 1.1 times higher at 1 degree uncrossed disparity. This elevation value is near increment thresholds for contrast discrimination within a range of high contrasts ( Legge & Foley, 1980 ; Maehara & Goryo, 2005 ; Meese et al, 2006 ). Thus, the observers would possibly notice subtle changes in the appearance of the luminance contrasts of stereoscopic patterns even if the actual contrasts were kept constant.…”
Section: Discussionmentioning
confidence: 68%
“…This reveals a summation effect (the model is more sensitive to A 1 B than to A alone) at weak pedestal contrasts, but the dipper handles converge at higher contrasts where the denominator terms dominate the saturation constant, Z. This behaviour is found empirically in both the binocular (Legge, 1984;Maehara & Goryo, 2005;Meese et al, 2006) and spatial (Legge & Foley, 1980;Meese, Hess, & Williams, 2005;Meese & Summers, 2007) dimensions.…”
Section: Respmentioning
confidence: 66%
“…Two popular models, probability summation [8] and quadratic summation [5] , [9] , have been proposed for binocular combination of contrast signals near threshold. Power summation [7] , two-stage gain control [2] , twin summation [10] , and binocular normalization [33] , have been proposed for supra-threshold binocular contrast combination. Because the relative phase between monocular images was set to zero in these studies, the phase information was absent in these models.…”
Section: Discussionmentioning
confidence: 99%